Variasi padat penebaran terhadap pertumbuhan ikan Patin (Pangasius hypophthalmus) yang dipelihara dalam keramba - - Mardani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This experiment provides an overview on the stocking density of catfish. Its purpose is to know the influence of stocking density variation on the growth of Striped catfish (Pangasius hypophthalmus) which is maintained in cage. The best results in this experiment was the stocking density of 10 tail/cage. Key words : Striped catfish (Pangasius hypophthalmus), Growth, stocking density, cage.